Evaluation of personality traits in social phobia patients (Archives of Clinical Psychiatry, 2010)
BACKGROUND: The symptoms of personality disorders (Axis II) commonly found in social phobia patients overlap highly with the symptoms that typify the Axis I disorder and are thus linked to diagnostic process in symptomatic patients. OBJECTIVE: The aim of the present study was to evaluate personality traits of social phobia patients. METHOD: One hundred and eight subjects were selected, from 18 to 65 years of age, who fulfilled the criteria of social phobia. The Cloninger's Temperament and Character Inventory (TCI) was applied. RESULTS: Social phobia patients differed in normalized data in the following personality traits: Novelty Seeking, Harm Avoidance, Persistence, Self Directedness, and Self-Transcendence. DISCUSSION: These findings point to a high overlap between Cloninger's description of the observed predominant personality traits and DSM-IV Axis I symptoms description for social phobia.